Assessment of the Effect of Macromolecular Crowding on Aggregation Behaviour of a Model Amyloidogenic Peptide - Gaharwar, Bharti; Gour, Shalini; Kaushik, Vibha; Gupta, Nimisha; Kumar, Vijay; Hause, Gerd; Kant Yadav, Jay (Protein and Peptide Letters, 2015)
Accumulation of ordered protein aggregates (or amyloids) represents a hallmark of many diseases (e.g., Alzheimer’s disease, type II diabetes, Parkinson’s diseases etc.), results from intermolecular association of partially unfolded proteins/ peptides. Such associations usually take place in highly crowded conditions. The aggregates, which are formed under in vitro and in vivo conditions exhibit substantial variations in their structure and function. Such heterogeneities in amyloids might arise due to macromolecular crowding that is usually omitted under in vitro conditions. The current study is an attempt to assess the effects of macromolecular crowding on amyloid formation using a model amyloidogenic peptide. The sequence of the peptide was derived from C-terminal region (RATQIPSYKKLIMY) of PAP(248-286), which naturally occurs in human semen as amyloid aggregates and is known for boosting HIV infectivity. This model peptide forms sedimentable and fibrillar aggregates in aqueous buffer and shows the characteristic features of amyloids. In the presence of macromolecular crowders the morphological features of the amyloids are significantly altered and resulted in the formation of shorter amyloid aggregates. The current study assumes the hypothesis that macromolecular crowding in the biological system favours formation of heterogeneous classes of aggregates and each of them might differ in their biophysical and biological properties.
Keywords: macromolecular crowding